Premonitory Urges and Their Link With Tic Severity in Children and Adolescents With Tic Disorders - Kyriazi, Maria; Kalyva, Efrosini; Vargiami, Efthymia; Krikonis, Konstantinos; Zafeiriou, Dimitrios (Frontiers in Psychiatry, 2019)
Tics wax and wane regarding their severity, while their expression is affected by non-motor sensory or cognitive elements that are mostly known as ‘premonitory urges’. Since premonitory urges are often used in non-pharmacological interventions to decrease tic severity, it is of interest in the present study to examine whether premonitory urges can actually predict tic severity. 52 children and adolescents diagnosed with tics and Tourette syndrome (29 children with provisional tic disorder, 16children with chronic motor tic disorder, and 7 children with Tourette syndrome) were included in the study. Their age ranged between 6 to 15.7 years (mean age 9 years and 2 months). All participants completed the YGTSS (Yale Global Tic Severity Scale) in order to assess tic severity and the Premonitory Urge for Tics Scale (PUTS) to measure premonitory urges (PU). Regression analysis revealed that PU were present at a higher rate in older subjects (>12 years of age) than in younger children and with a higher level of tic severity. Although the presence of PU was associated with tic severity across the entire age range, there was a stronger association between PU and tic severity in older children. A better insight into the pathophysiology of premonitory urges could possibly lead to the identification of new therapeutic modalities targeting the sensory initiators of tics in future research.